A novel real-time monitoring and control system for waste-to-energy gasification process employing differential temperature profiling of a downdraft gasifier - Chan, Wei Ping (2020)
A novel, cost-effective and real-time process monitoring and control system was developed to maintain stable operation of waste-to-energy gasification process. It comprised a feedback loop control that utilized the differential temperatures of the oxidation and reduction zones in the gasifier to determine the regional heat-flow (endothermic or exothermic), to assess the availability of oxidizing agent (for instance, air or O2) at the char bed and to calculate the fuel feeding rate. Based on the correlations developed, the air-to-fuel ratio or the equivalence air ratio (ER) for air gasification could be instantaneously adjusted to maintain stable operation of the gasifier. This study demonstrated a simplification of complex reaction dynamics in the gasification process to differential temperature profiling of the gasifier. The monitoring and control system was tested for more than 70 h of continuous operation in a downdraft fixed-bed gasifier with refuse-derived fuel (RDF) prepared from municipal solid wastes (MSW). With the system, fuel feeding rate could be adjusted accurately to stabilize the operating temperature and ER in the gasifier and generate syngas with consistent properties. Significant reductions in the fluctuations of temperature profiles at oxidation and reduction zones (from higher than 100 °C to lower than 50 °C), differential temperatures (from ±200 to ±50 °C) in gasifier and the flow rate (from 16 ± 6.5 to 12 ± 1.8 L/min), composition of main gas components, LHV (from 6.2 ± 3.1 to 5.7 ± 1.6 MJ/Nm3) and tar content (from 8.0 ± 9.7 to 7.5 ± 4.2 g/Nm3) of syngas were demonstrated. The developed gasifier monitoring and control system is adaptable to various types (updraft, downdraft, and fluidized-bed) and scales (lab, pilot, large scale) of gasifiers with different types of fuel.